Key competencies for sustainable practices of workers in the legal community in Mexico - Contreras-Arámbula, Alexis; Sánchez-Cano, Julieta Evangelina (Renewable Energy, Biomass & Sustainability, 2024)
Today’s world faces great challenges because of the knowledge era and globalization. Key issues, such as environmental degradation, call for an urgent need to raise awareness among the workforce to act in a more planet-friendly manner. Recent studies reveal that 6 of the 9 planetary limits that allow life on Earth have already been exceeded. UNESCO suggests that a paradigm shift can only be achieved through competency-based education, where key sustainability skills that cut across specific competencies are coerced and help employees act consciously. This study tries to assess the extent to which the competencies currently requested to occupy the position of jurist are aligned with frameworks of competences adjusted to sustainability. To achieve this, a monitoring was carried out in the legal area of Internet work bags using web scraping techniques, the search produced 291 records of which 85 competencies were obtained, which were reduced to 14 by deductive methods with the help of ATLAS.ti. In addition, theoretical relationships were sought between the skills recovered and the sustainable competencies considered in the framework proposed by UNESCO in 2017, with the aim of obtaining data and obtaining statistics with the help of EXCEL and R Studio, and with this in mind establishing convergences. The findings suggest that employers prefer technical competencies (58.75%) over soft ones, more focused on sustainable performance (41.25%). On the other hand, it may be suggested that the skills collected could be key to developing scales of measurement of sustainable performance in employees carrying out legal tasks.